SPECIAL COLLOQUIAL WORDS ARE BEST WAY TO DEPICT THE MAIN CHARACTER’S REAL SCRATCH TO THE READER - Berdiyeva Nasiba (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In our regular talks with our friends and family, we frequently hear and utilize colloquial language. Authors utilize colloquial language because it is seen as a literary device. The reader may find people more believable and sympathetic as individuals with diverse economic status and cultural backgrounds when they use colloquialisms in their speech. The definition of colloquial language will be discussed in this piece along with several real-world and literary examples. It will also take into account the reasons for and effects of the use of colloquial language.